Theory of Inverse Edelstein Effect of The Surface States of A Topological Insulator - H. Geng (Nature Portfolio, 2017)
Abstract The surface states of three-dimensional topological insulators possess the unique property of spin-momentum interlocking. This property gives rise to the interesting inverse Edelstein effect (IEE), in which an applied spin bias μ is converted to a measurable charge voltage difference V. We develop a semiclassical theory for the IEE of the surface states of Bi2Se3 thin films, which is applicable from the ballistic regime to diffusive regime. We find that the efficiency of the spin-charge conversion, defined as γ = V/μ, exhibits a universal dependence on the ratio between sample size and electron mean free path. The efficiency increases from γ = π/4 in the ballistic limit to γ = π in the diffusive limit, suggesting that sufficient strength of impurity scattering is favorable for the IEE.